NUMERICAL MODELLING OF THE THERMAL EVOLUTION OF THE NORTHWESTERN DNIEPR-DONETS BASIN (UKRAINE) - Shymanovskyy V.A.; Sachsenhofer R.F.; Izart A.; Li Y. (My University, 2004)
The Dniepr–Donets Basin (DDB) is a Late Devonian rift structure located within the East-European Craton. Numerical heat flow models for 13 wells calibrated with new maturity data were used to evaluate temporal and lateral heat flow variations in the northwestern part of the basin.The numerical models suggest that heat flow was relatively high during Late Carboniferous and/or Permian times. The relatively high heat flow is probably related to an Early Permian re-activation of tectonic activity. Reconstructed Early Permian heat flow values along the axial zone of the rift are about 60 mW/m2 and increase to 90 mW/m2 along the northern basin margin. These values are higher than those expected from tectonic models considering a single Late Devonian rifting phase. The calibration data are not sensitive to variations in the Devonian/Carboniferous heat flow. Therefore, the models do not allow deciding whether heat flows remained high after the Devonian rifting, or whether the reconstructed Permian heat flows represent a separate heating event.Analysis of the vitrinite reflectance data suggest that the northeastern Dniepr–Donets Basin is characterised by a low Mesozoic heat flow (30–35 mW/m2), whereas the present-day heat flow is about 45 mW/m2.
Keywords: Heat flow; Dniepr – Donets Basin; Syn-rift phase; Post-rift phase; Thermal evolution; Basin modelling; Biomarker; Vitrinite reflectance; Paleozoic::Devonian; Палеозой::Девонская